Pengaruh Model Pembelajaran Kooperatif dan Gaya Belajar Kognitif Siswa terhadap Keterampilan Proses Sains - Ai Jamilah; Dwi Dani Apriyani; Erlando Doni Sirait (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The purpose of this study was to determine the effect of the Cooperative Learning Model and Students' Cognitive Learning Styles on Science Process Skills in Cisaat Senior High School, Sukabumi Regency in the 2015/2016 academic year towards 80 students. Data collection techniques were carried out on the variable cooperative learning model with documentation, data on cognitive learning styles with a questionnaire and data on science processing skills with a treatment. This research was conducted with an experimental method. From the research results, it was found that there was an effect of the cooperative learning model on science process skills, the influence of students' cognitive learning styles on science process skills and the influence of the interaction of cooperative learning models and cognitive learning styles on science process skills in Cisaat Senior High School, Sukabumi Regency.